Macular Bruch´s membrane length and axial length: the Beijing Eye Study - Jonas, Jost B. (PLOS ONE, 2015)
Purpose: To assess whether macular Bruch´s membrane gets lengthened in axial myopia. Methods: Using the enhanced depth imaging mode of spectral-domain optical coherence tomography and examining a subgroup of participants of the population-based cross-sectional Beijing Eye Study, we measured the length of Bruch´s membrane (“MacBMLength”) from the fovea to the temporal edge of parapapillary gamma zone, and the distance between the fovea and the temporal optic disc border. Parapapillary gamma zone was defined as the parapapillary region without Bruch´s membrane. We additionally measured ocular biometric parameters and assessed non-ophthalmologic variables. Results: Measurements of MacBMLength were performed on 322 individuals. MacBMLength (mean: 3.99±0.33 mm; range: 3.17-4.93 mm) was not significantly associated with any systemic parameter or ocular biometric parameter. Gamma zone width (mean: 0.18±0.30mm; range: 0.00-2.61mm) was associated (multivariate analysis; correlation coefficient r:0.80) with longer axial length (P<0.001; standardized correlation coefficient beta: 0.60; non-standardized correlation coefficient B:0.11; 95%CI: 0.09,0.14) and with longer fovea-optic disc border distance (P<0.001; beta:0.28; B:0.19; 95%CI:0.14,0.25), but not with MacBMLength (P = 0.42). Fovea-temporal disc border distance (mean: 4.16±0.44mm; range: 3.17-5.86mm) was associated (overall correlation coefficient: 0.68) with longer axial length (P<0.001; beta: 0.36; B: 0.10; 95%CI: 0.06, 0.13), after adjusting for flatter anterior chamber depth (P = 0.003; beta:-0.14; B:-0.14; 95%CI: -0.23,-0.05) and wider parapapillary gamma zone (P<0.001; beta:0.42; B:0.62; 95%CI:0.44,0.81). Conclusions: In contrast to parapapillary gamma zone width and fovea-disc border distance, MacBMLength was not significantly associated with axial length. Axial elongation associated increase in fovea-disc distance may predominantly occur through development or elongation of parapapillary gamma zone, while macular Bruch´s membrane may mostly be independent of axial elongation.
Gesehen am 19.02.2018